2009
DOI: 10.1037/a0015449
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining the relationships between racial identity, cultural mistrust, help-seeking attitudes, and preference for a Black counselor.

Abstract: The purpose of the present study was to examine the extent to which Black racial identity attitudes, cultural mistrust, and help-seeking attitudes predicted preference for a Black counselor in a sample of 168 African American adults. Participants were recruited from college and community settings in an urban, southern location in the United States. Participants completed 4 self-report measures: the Cross Racial Identity Scale (B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 42 publications
4
62
0
Order By: Relevance
“…Although no research has examined the association between racial identity and health care mistrust, other studies have examined the relationship between racial identity and global cultural mistrust, and have found cultural mistrust to be strongly and positively correlated with Black racial identity. 40,41 The total GBMMS was associated with residential racial segregation such that participants in census tracts with a high proportion of Blacks had higher GBMMS scores than those in tracts with a lower proportion. While no studies have examined this association, the possibility that medical mistrust is a consequence of segregation is raised by a small but growing literature outlining the role of residential segregation as a fundamental social determinant of health that limits access to quality health care.…”
Section: Discussionmentioning
confidence: 99%
“…Although no research has examined the association between racial identity and health care mistrust, other studies have examined the relationship between racial identity and global cultural mistrust, and have found cultural mistrust to be strongly and positively correlated with Black racial identity. 40,41 The total GBMMS was associated with residential racial segregation such that participants in census tracts with a high proportion of Blacks had higher GBMMS scores than those in tracts with a lower proportion. While no studies have examined this association, the possibility that medical mistrust is a consequence of segregation is raised by a small but growing literature outlining the role of residential segregation as a fundamental social determinant of health that limits access to quality health care.…”
Section: Discussionmentioning
confidence: 99%
“…The failure to engage with treatment may also be explained by the stigmatized views of mental health treatment held by African Americans (Primm, Osher, & Gomez, 2005). Studies indicate that African American clients prefer, and have improved treatment engagement with, African American clinicians, who are rarely available (Manderscheid & Henderson, 2001;Substance Abuse and Mental Health Services Administration, 2010;Townes, Chavez-Korell, & Cunningham, 2009). When negative termination is due to additional criminal activity, environmental factors, such as poverty, neighborhood influence, and stress, may play a role in such criminal behavior (Sampson & Wilson, 2005).…”
Section: Dirks-linhorst Et Almentioning
confidence: 96%
“…Initially developed as a concept to describe the distrust Black Americans had towards White Americans, cultural mistrust encompasses an overall mistrust of White-dominated institutions such as the legal system, educational system, job settings, and government agencies (David, 2010). Many studies found that cultural mistrust resulted in a preference by Black clients for Black counselors, negative attitudes toward seeking psychological treatment, and a propensity to terminate therapy prematurely (Sue & Sue, 1972;Townes, Chavez-Korell, & Cunningham, 2009). These findings have been generalized to other minority groups including Southeast Asians and Latinos (David, 2010;Shea & Yeh, 2008).…”
Section: Cultural Mistrust Of Mental Health Counselorsmentioning
confidence: 99%